DESCRIPTION OF HARMONIC QUASICONFORMAL MAPPINGS - Anila Duka (European Scientific Journal, ESJ, 2014)
In this paper we will discuss harmonic functions, conformal mappings and quasiconformal mappings and their applications, ect .Which are more flexible than conformal mappings and this make them an easy tool. Conformal mappings degenerate when they are generalized with manny variables, but quasiconformal mappings don’t.